IDENTIFICATION OF ELECTROMAGNETIC FIELDS RADIATION INTENSITY ON MEDIUM VOLTAGE NETWORK EQUIPMENT - Siregar, Niko; Kurnianto, Rudi; Imansyah, Fitri; Yacoub, Redi; Kusumawardhani, Eka (Faculty of Engineering, Universitas Tanjungpura, 2023)
This research is about how to identify electromagnetic fields radiation intensity with measuring the electric fields and magnetic fields then compare it to the radiation exposure standards for public from ICNIRP. With the experimental method directly to the 15 randomize research sites in Pontianak city, each measurement on 1 site done on 4 sides, front, back, right and left of the objects and each sides done measurement 5 times on different distance from 1